Invasive Pulmonary Aspergillosis after Recent Influenza in a Child with Acute Myeloid Leukemia - Kim, Beom-Joon; Kim, Seong koo; Han, Seung Beom; Lee, Jae Wook; Yoon, Jong-Seo; Chung, Nack-Gyun; Cho, Bin; Kang, Jin Han; Kim, Hack-Ki (Clinical pediatric hematology-oncology, 2015)
Respiratory viral infection has been reported as a risk factor for invasive pulmonary aspergillosis (IPA) in hematopoietic cell transplantation (HCT) recipients, and IPA following influenza has been reported. We report a 13-year-old boy diagnosed with IPA following influenza. He received allogeneic HCT and then received glucocorticoids for chronic graft-versus-host disease. On admission, he complained of non-neutropenic fever and dyspnea. He was diagnosed with influenza A via a polymerase chain reaction (PCR) test from nasopharyngeal swab, and oseltamivir was administered. Fever re-emerged nine days later and repeat PCR was positive for influenza A. His fever did not resolve despite triple antiviral and empirical antibiotic therapy. On hospital day 22, IPA was diagnosed based on chest computed tomography and positive serum galactomannan results, and his symptoms improved with voriconazole therapy. However, he died of uncontrolled bronchiolitis obliterans on hospital day 128. IPA should be considered a complication of influenza in immunocompromised children. KCI Citation Count: 0